Influence of the velocity gradient of the carrier medium on the crushing characteristics of non-Newtonian liquid droplets on the example of a highly concentrated coal-water suspension; Experimental Thermal and Fluid Science; Vol. 171 - Kuznetsov G. V. Geny Vladimirovich; Syrodoy S. V. Semen Vladimirovich; Zamaltdinov R. R. Roman Rinatovich; Solodovnikova Zh. A. Zhanna Andreevna; Borisov B. V. Boris Vladimirovich; Nigay N. A. Nataljya Andreevna; Gutareva N. Yu. Nadezhda Yurievna; Tamashevich Maksim M. (2026, 2026)
Title screen